Sociabilidade e cultura: a história dos pequenos teatros na cidade de Manaus (1859-1900) - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The dissertation called Sociability and Culture. The History of the small theaters in the city of Manaus (1859-1900) approaches the cultural expressions of the amazonian society during the provincial period, focusing on the first theaters of the city: the Straw Theater described by the German traveller Robert Ave-Lallemant, the Comic Variety Theater, from Lima Penante, the Portuguese Beneficient Theater and the Paradise Theater, all of them builded before the sumptuous Amazon Theater. Basing on the rules of the New Cultural History, it is concerning the study of a previous moment to the great production of the rubber, when the spaces of the city and the customs of its inhabitants started to modify and to mold to the European style. The research used bibliographical sources and registers, no matter they had been explored beyond some texts that theoretically base the periodic task, at the of the 19th century and at the beginning of the 20th century. We also appeal to other researches on the subject, that analyze the same time, even in other provinces. The objective was to put in practice the exercise of the comparison, that is a basic attitude in the historical analysis. In this context, the first aspects on civilization that arrived to Manaus were examined, the european clothes and the ways of behavior in public, everything from the emphasis of the theater manifestations, that traied to entertain the population, and at the same time, to educate it, in the aspect of the morality based on the bourgeois ideals, or the fine and educated held that was demanded in public. On the other hand, there were also studied the sociabilities and habits of the local inhabitants, like the balls, the religious parties, fishing, the baths in smalls rivers, and so on. One of the conclusions of this study is that even the subject demands inquiry continuity, there are few researches on the culture in that period. This points out amongst other things, the existence of a possible preconception on the subject: being the population composed basically by natives and their descendants, they would have leisure that they could not have relevance for this study: as if the European leisure and customs they only could be significant.
Keywords: História Nova; História da Cultura; Teatro - Manaus; CIÊNCIAS HUMANAS: HISTÓRIA